ANALISIS PERSEPSI SISWA TERKAIT PRESENCE DALAM PEMBELAJARAN IPA MENGGUNAKAN MEDIA PEMBELAJARAN AUGMENTED REALITY - Rieke Nur Fitria; Muhamad Arif Mahdiannur (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2026)
This study aims to analyze students' perceptions of Presence in augmented reality (AR)-based science learning, which includes the dimensions of spatial Presence, Social Presence, and Self- Presence, and to examine the differences in Presence based on previous AR experience and the relationship between Presence dimensions. A quantitative approach with a survey method was used, involving 335 ninth-grade students of Public Junior High Schools in Krian District, Sidoarjo Regency from SMPN 1 Krian, SMPN 2 Krian, and SMPN 3 Krian. The instrument used was the Augmented Reality Presence Scale (ARPS) consisting of 21 items with a 5-point Likert scale. Data analysis included descriptive statistics, independent t-test, and Pearson correlation. The results revealed that students' Presence perceptions were in the high category (M = 3.70), with the highest Social Presence score (M = 3.85), followed by spatial Presence (M = 3.68), and Self-Presence (M = 3.55). Significant differences were found in all dimensions of Presence between students with and without prior AR experience, with medium to large effect sizes (d = 0.701 – 0.835). Three dimensions of Presence showed a strong positive correlation (r = 0.793 – 0.871). This study concluded that AR technology effectively creates immersive learning experiences, although Self-Presence still needs improvement. It is recommended that teachers provide technology orientation sessions before instruction and that media developers integrate narrative elements to enhance student emotional engagement. ABSTRAKPenelitian ini bertujuan untuk menganalisis persepsi siswa tentang Presence dalam pembelajaran IPA berbasis augmented reality (AR), yang mencakup dimensi spatial presence, social presence, dan self-presence, serta untuk mengkaji perbedaan Presence berdasarkan pengalaman AR sebelumnya dan hubungan antar dimensi Presence. Pendekatan kuantitatif dengan metode survei digunakan, melibatkan 335 siswa kelas IX SMP Negeri di Kecamatan Krian, Kabupaten Sidoarjo yang berasal dari SMPN 1 Krian, SMPN 2 Krian, dan SMPN 3 Krian. Instrumen yang digunakan adalah Augmented Reality Presence Scale (ARPS) yang terdiri dari 21 item dengan skala Likert 5 titik. Analisis data meliputi statistik deskriptif, uji-t independen, dan korelasi Pearson. Hasil penelitian mengungkapkan bahwa persepsi Presence siswa berada pada kategori tinggi (M = 3,70), dengan skor social presence tertinggi (M = 3,85), diikuti oleh spatial presence (M = 3,68), dan self-presence (M = 3,55). Perbedaan yang signifikan ditemukan di semua dimensi Presence antara siswa dengan dan tanpa pengalaman AR sebelumnya, dengan ukuran efek sedang hingga besar (d = 0,701 – 0,835). Tiga dimensi Presence menunjukkan korelasi positif yang kuat (r = 0,793 – 0,871). Studi ini menyimpulkan bahwa teknologi AR secara efektif menciptakan pengalaman belajar yang imersif, meskipun Presence diri masih membutuhkan perbaikan. Disarankan agar guru memberikan sesi orientasi teknologi sebelum pengajaran dan agar pengembang media mengintegrasikan elemen naratif untuk meningkatkan keterlibatan emosional siswa.